The odd power generalized Weibull-G power series class of distributions: Properties and applications - Broderick Oluyede; Thatayaone Moakofi; Fastel Chipepa (Statistics in Transition new series (SiTns), 2022)
We develop a new class of distributions, namely, the odd power generalized Weibull-G powerseries (OPGW-GPS) class of distributions. We present some special classes of the proposeddistribution. Structural properties, have also been derived. We conducted a simulation studyto evaluate the consistency of the maximum likelihood estimates. Moreover, two real dataexamples on selected data sets, to illustrate the usefulness of the new class of distributions.The proposed model outperforms several non-nested models on selected data sets.
Keywords: 519; Weibull-g distribution; power series; Poisson distribution; logarithmic distribution; maximum likelihood estimation